ChemInform Abstract: Synthesis of Substituted 2, 4, 5, 6‐Tetrahydrocyclopenta[c]pyrazoles and 2, 4, 5, 6‐Tetrahydropyrrolo[3, 4‐c]pyrazoles by Intramolecular Nitrilimine Cycloaddition. Issue 35 (2nd September 2014) - Winters, Michael P.; Teleha, Christopher A.; Sui, Zhihua
Abstract Treatment of sensitive hydrazonyl chlorides with triethylamine results in the formation of nitrilimine intermediates.